About One Cloud Computing Simulation Model - Golosov, P. E.; Gostev, I. M. (2021 Systems of Signals Generating and Processing in the Field of on Board Communications, 2021)
Today, the use of cloud resources is becoming increasingly popular. On the one hand, it is mere data storage and their respective sharing by a number of users, on the other hand, it is the opportunities that open up following large computing resources available "in the cloud". An important aspect is the hash function search technologies and adjusting approaches to managing computing resources due to the specifics of their service algorithms. The article considers a simulation model for a computational process built in the Simulink environment (SimEvent) and based on the queueing theory of a G/G/n/inf. system with a set of input streams, an infinite queue, two feedbacks formed by re-processing a request in case of a device failure, and because of the possibility of an extranonce situation and its handling. The results of modeling are considered for different input flows - deterministic, uniformly distributed, Poisson and exponential, with different service disciplines and different laws of processing requests in the queue. The advantages and disadvantages of the proposed model are analyzed in comparison with the well-known methods of controlling input streams (scheduling tasks in operating systems).